Women`s perspectives of personal trainers: a qualitative study - Melton, D.; Dail, T. K.; Katula, J. A.; Mustian, K. M. (The Sport Journal, 2011)
Abstract Personal trainers play an integral role in the day-to-day operation of the facilities in which they work. Research has identified a number of qualities and competencies necessary to be an effective exercise leader, but there is little scholarly work addressing clients` attitudes related to the performance of personal trainers. Utilizing focus group methodology, female clients of personal trainers were recruited to provide viewpoints related to the desirable qualities of personal trainers, as well as opinions regarding trainer certification and academic preparation. Responses of the participants were transcribed, coded, and analyzed for themes. Four global themes emerged: Selection Rationale, Personal Trainer Rationale, Loyalty Rationale and Negative Characteristics. Selection Rationale consisted of qualities that influence a client`s decision to hire a particular trainer (e.g., physique, results observed in other clients, social skills). Personal Trainer Rationale referred to the clients` reasons (e.g., frustration with current fitness level) for hiring a specific trainer. Loyalty Rationale referred to the credentials of a personal trainer that solidify the client/trainer relationship and Negative Characteristics referred to qualities considered unethical or unprofessional. The results suggest that undergraduate exercise science programs should devote additional time toward the development of future fitness trainers` affective qualities and that clients would benefit from information about the credentials of personal trainers.